Nutritional, economic, social, and governance implications of traditional food markets for vulnerable populations in sub-Saharan Africa: a systematic narrative review - Cook, Brian; Trevenen-Jones, Ann; Sivasubramanian, Bhavna (Frontiers in Sustainable Food Systems, 2024)
Traditional food markets in sub-Saharan Africa (SSA) are pivotal urban spaces, especially for vulnerable populations. These markets are vibrant hubs for commerce, cultural exchange, and social interaction, yet they face challenges such as food safety issues, inadequate infrastructure, and regulation that is a complex mix of informal mechanisms in need of a balanced degree of formalization. Rapid urbanization in SSA and the vulnerabilities of informal settlements underline their enduring importance. The COVID-19 pandemic further highlighted their crucial role in promoting food access, supporting local economies, and preserving social connections during crises. However, a comprehensive understanding of their multifaceted impact on urban life remains limited. This study provides a systematic narrative literature review with the aims of mapping the existing literature and evaluating their complex impact on vulnerable communities. The review employed a systematic search strategy, encompassing research studies and grey literature. It highlights the geographic distribution of studies across SSA, with a concentration in East and Southern Africa. Nutrition is the most explored theme, followed by governance, with economics and social aspects relatively underexamined. Traditional food markets are vital sources of affordable food for the urban poor and serve as pillars of economic mobility, providing livelihoods and employment opportunities, especially for women, and act as hubs for diverse groups to interact. Market governance is complex, often marked by policy misalignments due to insufficient collaboration among stakeholders. Policy initiatives to support traditional food markets in SSA should focus on formalization and contextaware regulations to enhance efficiency and vendor security, investment in market-related infrastructure, and nutrition-focused policies and economic support for vendors. Further research is needed to bridge thematic and regional gaps, and to inform evidence-based policy measures to support these vital urban institutions.